Optimizing a modified cetyltrimethylammonium bromide protocol for fungal DNA extraction: Insights from multilocus gene amplification - Dar Gulam Jeelani; Nazir Ruqeya; Wani Shakil A.; Farooq Saleem; Aziz Tariq; Albekairi Thamer H. (Open Life Sciences)
Genomic DNA (gDNA) extraction is an important step in many molecular studies of fungal biology, and it is necessary to evaluate the efficiency, cost-effectiveness, and efficacy of different extraction methods to ensure successful amplification of the target gene and minimize deoxyribonucleic acid (DNA) degradation. The modified cetyltrimethylammonium bromide (CTAB) method was found to be effective in releasing high molecular weight gDNA with minimal protein contamination. Based on anticipated gDNA yield and quality, extraction time, cost effectiveness, successful amplification, and waste management, our findings serve as a guide for selecting techniques of gDNA extraction from fungal species. This study presents a modified CTAB method for extracting DNA from a variety of fungal species including Aspergillus, Penicillium, Alternaria, Dothiorella, and Fusarium. Comparison of three cell crushing methods reveals similar gDNA yields, demonstrating the method’s effectiveness. Furthermore, the modified CTAB method is cost-effective and safe, eliminating the need for grinding with liquid nitrogen or bead beating. The method has a potential use for nucleic-based fungal disease diagnosis such as fish fungal diseases, plant pathogens, fruit rot associated pathogens, and human fungal diseases as we were successful in PCR amplifying several gene loci from varied fungal pathogens.